Comparative Analysis of Qualitative and Bioactive Compounds of Whole and Refined Flours in Durum Wheat Grains with Different Year of Release and Yield Potential - Valeria Menga; Valentina Giovanniello; Michele Savino; Antonio Gallo; Salvatore Antonio Colecchia; Vanessa De Simone; Silvia Zingale; Donatella Bianca Maria Ficco (Plants, 2023)
Durum wheat varieties are important sources of nutrients and provide remarkable amounts of phytochemicals. Especially, phenolics, which are mostly located in external layers of grains, have recently gained increased interest due to their high antioxidant power. This study aimed to evaluate the differences in the quality traits and phenolic compounds’ concentration (e.g., phenolic acids) of different durum wheat genotypes, namely four Italian durum wheat cultivars and a USA elite variety, in relation to their yield potential and year of release. Phenolic acids were extracted both from wholemeal flour and semolina and analysed through HPLC-DAD analysis. Ferulic acid was the most represented phenolic acid, both in the wholemeal flour (438.3 µg g−1 dry matter) and in semolina (57.6 µg g−1 dry matter) across all cultivars, followed by p-coumaric acid, sinapic acid, vanillin, vanillic acid, syringic acid, and p-hydroxybenzoic acid. Among the cultivars, Cappelli showed the highest phenolic acid content, whilst Kronos had the lowest one. Negative correlations occurred between some phenolic acids and morphological and yield-related traits, especially for Nadif and Sfinge varieties. On the contrary, durum wheat genotypes with low yield potential such as Cappelli accumulated higher concentrations of phenolic acids under the same growing conditions, thereby significantly contributing to the health-promoting purposes.